Zinc and genital infections. Issue 4 (August 1987) - Cornell, M S; Hinks, L J; Singha, H S; Walker, V; Willmott, F E
Abstract : The zinc status of 19 patients with chronic or recurrent genital infections and 18 patients with non-recurrent genital infections was assessed by measuring plasma and leucocyte zinc concentrations. Neither group of patients had plasma or leucocyte zinc concentrations that differed significantly from those of matched healthy controls. Each of six patients with chronic candidiasis had anergy to candidal antigen, as shown by delayed cutaneous hypersensitivity to intradermal injection of the antigen, but their zinc status was normal. This study provided no evidence of zinc deficiency in this small number of patients with acute non-recurrent or chronic recurrent genital infections.